Role of User-Generated Content, Key Opinion Leader, Virtual Community, and Culture in Shaping Pro-Environmental Behavior: Propositions and Conceptual Framework - Daniel Sanjaya; Asnan Furinto; Mohammad Hamsal; Rano Kartono (Journal of International Conference Proceedings, 2022)
This paper aims to provide a conceptual framework of how tourists’ pro-environmental behavior is shaped by examining the role of User-Generated Content (UCG), Key Opinion Leader (KOL), virtual community, and culture. This framework is required, as the current literature mainly discusses about the role of KOL that influences consumer purchasing behavior in retail and health industry. There is lack of research that focuses on role of KOL and its supporting element (UCG and virtual community) to influence tourists’ pro-environmental behavior. The method of this research uses literature review. From literature review, it finds that researchers proposed several antecedent variables to predict tourists’ pro-environmental behavior. This paper also outlines nine research propositions and suggest methods for further research. Keywords: user-generated content, key opinion leader, virtual community, culture, tourists’ pro-environmental behavior.